Gustatory dysfunction and oral ulceration in COVID-19 patients: A cross sectional study - Mayank Hans; Veenu Madaan Hans; Namrata Kahlon; Mayank Sagar; Anil Kumar Pandey; Asim Das (Wolters Kluwer Medknow Publications, 2022)
Background: Over the past year, patients infected by severe acute respiratory syndrome coronavirus-2 presented with severe gustatory dysfunction, the prevalence of which varies among different populations. Furthermore, there have been sporadic reports of oral ulceration observed in coronavirus disease-19 (COVID-19) patients due to varied reasons. The aim of this study was to investigate and characterize the presence of gustatory disorders, oral ulceration, and other oral changes in patients with laboratory-confirmed COVID-19 infection. Materials and Methods: In this cross-sectional observational study, a total of 402 participants who were detected COVID-19 positive by reverse transcription-polymerase chain reaction were included. Their demographic and clinical data were recorded through hospital records. The participants were interviewed either in person or on the telephone to record any change in taste and/or changes within the oral cavity. t-test for independent means was used to compare mean age, while other characteristics were compared by Chi-square test and Z-score test. P < 0.05 was taken as significant. Results: Out of the total sample of 402 individuals, 262 were male and 140 were female. The prevalence of gustatory dysfunction and oral ulceration was 43.53% and 15.67%, respectively, in the studied sample. Significantly more females had gustatory dysfunction than males and older subjects more commonly than younger. The symptom of loss/change of taste and oral ulceration were more probable to occur together. In addition, the tongue was the most common site for ulceration in our studied sample. Conclusion: Loss of taste is a common symptom of COVID-19 patients, whereas oral ulceration is not so commonly reported. However, the presence of both these symptoms could impair the quality of life of patients and hamper adequate nutritional uptake.